Skin friction reduction on smooth and rough surfaces using air lubrication - Jonathan L. Carter; Victoria M. Hynes; J. Travis Hunsucker (Ocean Engineering, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Innovative In Vitro-In Silico Platform for Dose–Response Modeling in Canine Bladder Cancer: A 3D Organoid- and Mathematics-Based Approach - Mackenzie Long; Yvonne Peng; Saumya Gade; Hannah Nicholson; Michael Catucci; Christopher Zdyrski; Aleksandra Pawlak; Megan Corbett; Corey Saba; Travis Laver; Emily Rawlings; Maria Orbay-Cerrato; et al. (The AAPS Journal, 2026)

Pregnancy and Postpartum Effects of Electronic Cigarettes on Maternal Health and Vascular Function in the Fourth Trimester - Amber Mills; Duaa Dakhlallah; Anand Ranpara; W. Travis Goldsmith; Paul D. Chantler; Yue-Wern Huang; Jonathan Boyd; I. Mark Olfert (Cardiovascular Toxicology, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Effect of alkali-silica reaction on the flexural behavior of beams with tensile lap splices - Travis Thonstad; Jonathan M. Weigand; Fahim Sadek; Adam L. Pintar; Sorin Marcu; Timothy J. Barrett; Long T. Phan (Engineering Structures, 2024)

Population genomic structure of a widespread, urban‐dwelling mammal: The eastern grey squirrel ( Sciurus carolinensis ) - Nicole A. Fusco; Bradley J. Cosentino; James P. Gibbs; Maximilian L. Allen; Alexander J. Blumenfeld; George H. Boettner; Elizabeth J. Carlen; Merri Collins; Catherine Dennison; Devin DiGiacopo; André‐Philippe Drapeau Picard; Jonathan Edmonson; et al. (Molecular Ecology, 2024)
Urbanization is a persistent and widespread driver of global environmental change, potentially shaping evolutionary processes due to genetic drift and reduced gene flow in cities induced by habitat fragmentation and small population sizes. We tested this prediction for the eastern grey squirrel ( Sciurus carolinensis ), a common and conspicuous forest‐dwelling rodent, by obtaining 44K SNPs using reduced representation sequencing (ddRAD) for 403 individuals sampled across the species' native range in eastern North America. We observed moderate levels of genetic diversity, low levels of inbreeding, and only a modest signal of isolation‐by‐distance. Clustering and migration analyses show that estimated levels of migration and genetic connectivity were higher than expected across cities and forested areas, specifically within the eastern portion of the species' range dominated by urbanization, and genetic connectivity was less than expected within the western range where the landscape is fragmented by agriculture. Landscape genetic methods revealed greater gene flow among individual squirrels in forested regions, which likely provide abundant food and shelter for squirrels. Although gene flow appears to be higher in areas with more tree cover, only slight discontinuities in gene flow suggest eastern grey squirrels have maintained connected populations across urban areas in all but the most heavily fragmented agricultural landscapes. Our results suggest urbanization shapes biological evolution in wildlife species depending strongly on the composition and habitability of the landscape matrix surrounding urban areas.

Diet Quality of Young Children in the US-Affiliated Pacific’s Children’s Healthy Living (CHL) Program - Rica Dela Cruz; Rachel Novotny; Lynne R. Wilkens; Yurii B. Shvetsov; Ashley B. Yamanaka; Jean Butel; Tanisha F. Aflague; Patricia Coleman; Leslie Shallcross; Jonathan Deenik; Victoria Lee R. Mapa; Carol J. Boushey; et al. (Journal of the Academy of Nutrition and Dietetics, 2023)

Towards improved conversion of wet waste to jet fuel with atomic layer deposition-coated hydrodeoxygenation catalysts - W. Wilson McNeary; Jacob H. Miller; Sean A. Tacey; Jonathan Travis; Gabriella D. Lahti; Michael B. Griffin; Katherine L. Jungjohann; Glenn Teeter; Tugce Eralp Erden; Carrie A. Farberow; Luke Tuxworth; Michael J. Watson; et al. (Chemical Engineering Journal, 2023)

Simulating cookiecutter shark bites with a 3D-printed jaw-dental model - Mark A. Grace; Daniel Huber; Kevin Travis; Michael H. Doosey; Jonathan Ford; Summer Decker; Justin Mann (Zoomorphology, 2023)
Ectoparasitic cookiecutter sharks (Chondrichthyes: Squaliformes: Dalatiidae; Isistius ) share common features for jaw and teeth structure, in particular, robust lower jaws and dignathic heterodonty (upper teeth crowns are more slender and shorter than the broader and longer lower teeth crowns). The jaws and teeth are well suited for feeding by excising a nearly symmetrical oval-flesh bite plug from a variety of prey species including marine mammals, fishes, and squids. There is considerable speculation regarding cookiecutter shark bite dynamics given that natural feeding behavior has not been observed. To elucidate cookiecutter shark bite dynamics, bites were experimentally simulated for the two cookiecutter shark species; the Cookiecutter Shark, Isistius brasiliensis (Quoy JRC, Gaimard, P (1824) Zoologie (3) Imprimerie royale) and the Largetooth Cookiecutter Shark, Isistius plutodus (Garrick JAF, Springer S (1964) Isistius plutodus, a new squaloid shark from the Gulf of Mexico. Copeia 678–682), using three-dimensional printed models of jaws with teeth. Bite simulations were conducted at standardized jaw bite-gape angles and ballistic gelatin was used to approximate prey flesh, from which aspect ratio analysis of bite wound geometrics was used to determine bite wound morphometrics for each species. The simulated bite experiment also was useful for assessing factors that potentially affect cookiecutter shark total length estimates when based on natural bite geometrics. In addition, the mechanics of producing experimental bites provide new insights related to the necessity for cookiecutter sharks to rotate their body to create nearly symmetrical oval bite wounds.

Mechanism of astatine and bismuth sorption on extraction chromatography resins from nitric acid media - Evgeny E. Tereshatov; Jonathan D. Burns; Steven J. Schultz; Brooklyn D. Green; Gabriela A. Picayo; Laura A. McCann; Lauren A. McIntosh; Gabriel C. Tabacaru; Austin Abbott; Matthew Berko; Emily Engelthaler; Kris Hagel; et al. (Chemical Engineering Journal, 2023)

Improving sightings-derived residency estimation for whale shark aggregations: A novel metric applied to a global data set - Gonzalo Araujo; Ariana Agustines; Steffen S. Bach; Jesse E. M. Cochran; Emilio de la Parra-Galván; Rafael de la Parra-Venegas; Stella Diamant; Alistair Dove; Steve Fox; Rachel T. Graham; Sofia M. Green; Jonathan R. Green; et al. (Frontiers in Marine Science, 2022)
The world’s largest extant fish, the whale shark Rhincodon typus , is one of the most-studied species of sharks globally. The discovery of predictable aggregation sites where these animals gather seasonally or are sighted year-round – most of which are coastal and juvenile-dominated – has allowed for a rapid expansion of research on this species. The most common method for studying whale sharks at these sites is photographic identification (photo-ID). This technique allows for long-term individual-based data to be collected which can, in turn, be used to evaluate population structure, build population models, identify long-distance movements, and assess philopatry and other population dynamics. Lagged identification rate (LIR) models have fewer underlying assumptions than more traditional capture mark recapture approaches, making them more broadly applicable to marine taxa, especially far-ranging megafauna species like whale sharks. However, the increased flexibility comes at a cost. Parameter estimations based on LIR can be difficult to interpret and may not be comparable between areas with different sampling regimes. Using a unique data-set from the Philippines with ~8 years of nearly continuous survey effort, we were able to derive a metric for converting LIR residency estimates into more intuitive days-per-year units. We applied this metric to 25 different sites allowing for the first quantitatively-meaningful comparison of sightings-derived residence among the world’s whale shark aggregations. We validated these results against the only three published acoustic residence metrics (falling within the ranges established by these earlier works in all cases). The results were then used to understand residency behaviours exhibited by the sharks at each site. The adjusted residency metric is an improvement to LIR-based population modelling, already one of the most widely used tools for describing whale shark aggregations. The standardised methods presented here can serve as a valuable tool for assessing residency patterns of whale sharks, which is crucial for tailored conservation action, and can cautiously be tested in other taxa.

Predicting moisture content during maize nixtamalization using machine learning with NIR spectroscopy - Michael J. Burns; Jonathan S. Renk; David P. Eickholt; Amanda M. Gilbert; Travis J. Hattery; Mark Holmes; Nickolas Anderson; Amanda J. Waters; Sathya Kalambur; Sherry A. Flint-Garcia; Marna D. Yandeau-Nelson; George A. Annor; et al. (Theoretical and Applied Genetics, 2021)

Diurnal changes in perineuronal nets and parvalbumin neurons in the rat medial prefrontal cortex - John H. Harkness; Angela E. Gonzalez; Priyanka N. Bushana; Emily T. Jorgensen; Deborah M. Hegarty; Ariel A. Di Nardo; Alain Prochiantz; Jonathan P. Wisor; Sue A. Aicher; Travis E. Brown; Barbara A. Sorg (Brain Structure and Function, 2021)

Genotyping by Multiplexed Sequencing (GMS) protocol in Barley - Jonathan Eagle; Travis Ruff; Marcus Hooker; Sajal Sthapit; Elliott Marston; Karol Marlowe; Dolores Covarrubias; Daniel Skinner; Patrick Hayes; Jamie Sherman; Deven See (Euphytica, 2021)
Genotyping by sequencing (GBS) and single nucleotide polymorphism (SNP) chip technologies are the primary SNP genotyping technologies used today. However, these genotyping technologies have some drawbacks that limit their usefulness in analysis. We have developed a robust protocol called genotyping by multiplexed sequencing (GMS) using SNP markers, providing informative genotypic data with greater flexibility. The genotypes derived from direct sequence reads reduce ambiguity in genetic analysis. The advantages of this protocol include: (1) This PCR-based direct sequencing protocol generates information from markers of interest and provides a more streamlined and accurate analysis process, by multiplexing hundreds of informative markers into a single sequencing run. (2) The marker sets are easily customized to the species of interest and can readily be changed. In this study we have taken the GMS protocol developed in wheat and adapted it to barley. We have identified 577 SNP markers that work well using this protocol providing adequate genome coverage for genomic selection and tag 267 QTL’s for genes of interest. Good markers have an adequate read depth of at least 5 amplicons and are reliably present across the population.

The Earth has humans, so why don’t our climate models? - Brian Beckage; Katherine Lacasse; Jonathan M. Winter; Louis J. Gross; Nina Fefferman; Forrest M. Hoffman; Sara S. Metcalf; Travis Franck; Eric Carr; Asim Zia; Ann Kinzig (Climatic Change, 2020)

Induced spawning and embryonic and early larval development of bonefish ( Albula vulpes ) - Williams R. Halstead; Sahar Mejri; Anthony C. Cianciotto; Paul S. Wills; Travis E. Van Leeuwen; Aaron J. Adams; Jonathan M. Shenker (Journal of Fish Biology, 2020)
Bonefish ( Albula vulpes L.) are a highly prized sport fish. Despite their economic importance, populations in the Florida Keys and Caribbean are in decline, with the early life history undescribed. Injections of carp pituitary extract into A. vulpes during the advanced stages of ovarian development induced ovulation and spawning. Embryos were sampled hourly until hatching into undeveloped, yolk‐sac leptocephalus larvae. These larvae survived 56 h post‐hatch, when myomeres and eyes were developing but not the mouth. These results inform future research on the reproduction and early life history of A. vulpes .

Ecological gradients drive insect wing loss and speciation: The role of the alpine treeline - Graham A. McCulloch; Brodie J. Foster; Ludovic Dutoit; Travis Ingram; Eleanor Hay; Andrew J. Veale; Peter K. Dearden; Jonathan M. Waters (Molecular Ecology, 2019)
Alpine ecosystems are frequently characterized by an abundance of wing‐reduced insect species, but the drivers of this biodiversity remain poorly understood. Insect wing reduction in these environments has variously been attributed to altitude, temperature, isolation, habitat stability or decreased habitat size. We used fine‐scale ecotypic and genomic analyses, along with broad‐scale distributional analyses of ecotypes, to unravel the ecological drivers of wing reduction in the wing‐dimorphic stonefly Zelandoperla fenestrata complex. Altitudinal transects within populations revealed dramatic wing reduction over very fine spatial scales, tightly linked to the alpine treeline. Broad biogeographical analyses confirm that the treeline has a much stronger effect on these ecotype distributions than altitude per se. Molecular analyses revealed parallel genomic divergence between vestigial‐winged (high altitude) and full‐winged (low altitude) ecotypes across distinct streams. These data thus highlight the role of the alpine treeline as a key driver of rapid speciation, providing a new model for ecological diversification along exposure gradients.

From low to high gear: there has been a paradigm shift in our understanding of evolution - David N. Reznick; Jonathan Losos; Joseph Travis (Ecology Letters, 2019)
Experimental studies of evolution performed in nature and the associated demonstration of rapid evolution, observable on a time scale of months to years, were an acclaimed novelty in the 1980–1990s. Contemporary evolution is now considered ordinary and is an integrated feature of many areas of research. This shift from extraordinary to ordinary reflects a change in the perception of evolution. It was formerly thought of as a historical process, perceived through the footprints left in the fossil record or living organisms. It is now seen as a contemporary process that acts in real time. Here we review how this shift occurred and its consequences for fields as diverse as wildlife management, conservation biology, and ecosystems ecology. Incorporating contemporary evolution in these fields has caused old questions to be recast, changed the answers, caused new and previously inconceivable questions to be addressed, and inspired the development of new subdisciplines. We argue further that the potential of contemporary evolution has yet to be fulfilled. Incorporating evolutionary dynamics in any research program can provide a better assessment of how and why organisms and communities came to be as they are than is attainable without an explicit treatment of these dynamics.

Erratum to: Visions of Restoration in Fire-Adapted Forest Landscapes: Lessons from the Collaborative Forest Landscape Restoration Program - Lauren S. Urgenson; Clare M. Ryan; Charles B. Halpern; Jonathan D. Bakker; R. Travis Belote; Jerry F. Franklin; Ryan D. Haugo; Cara R. Nelson; Amy E.M. Waltz (Environmental Management, 2017)

Visions of Restoration in Fire-Adapted Forest Landscapes: Lessons from the Collaborative Forest Landscape Restoration Program - Lauren S. Urgenson; Clare M. Ryan; Charles B. Halpern; Jonathan D. Bakker; R. Travis Belote; Jerry F. Franklin; Ryan D. Haugo; Cara R. Nelson; Amy E.M. Waltz (Environmental Management, 2017)

Cave development within a paleosol breccia in the dolomitized Seroe Domi Formation, Aruba, Lesser Antilles - Jonathan B. Sumrall; Jeanne L. Sumrall; Ryan W. Travis (Carbonates and Evaporites, 2016)

Tropical Cyclone Prediction Using COAMPS-TC - James Doyle; Richard Hodur; Sue Chen; Yi Jin; Jonathan Msokaitis; Shouping Wang; Eric Hendricks; Jao Jin; Travis Smith (Oceanography, 2014)

Variation in setal micromechanics and performance of two gecko species - Travis J. Hagey; Jonathan B. Puthoff; Madisen Holbrook; Luke J. Harmon; Kellar Autumn (Zoomorphology, 2014)

Discussions and decisions of the 2012–2014 International Committee on Taxonomy of Viruses (ICTV) Filoviridae Study Group, January 2012–June 2013 - Alexander A. Bukreyev; Kartik Chandran; Olga Dolnik; John M. Dye; Hideki Ebihara; Eric M. Leroy; Elke Mühlberger; Sergey V. Netesov; Jean L. Patterson; Janusz T. Paweska; Erica Ollmann Saphire; Sophie J. Smither; et al. (Archives of Virology, 2014)

Virus nomenclature below the species level: a standardized nomenclature for filovirus strains and variants rescued from cDNA - Jens H. Kuhn; Yīmíng Bào; Sina Bavari; Stephan Becker; Steven Bradfute; Kristina Brauburger; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; et al. (Archives of Virology, 2013)

Virus nomenclature below the species level: a standardized nomenclature for laboratory animal-adapted strains and variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; et al. (Archives of Virology, 2013)

Virus nomenclature below the species level: a standardized nomenclature for natural variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; Sven Enterlein; et al. (Archives of Virology, 2013)

Modeling the Yew Tree Tubulin and a Comparison of its Interaction with Paclitaxel to Human Tubulin - Jack A. Tuszynski; Travis J. A. Craddock; Jonathan Y. Mane; Khaled Barakat; Chih-Yuan Tseng; Melissa Gajewski; Philip Winter; Laleh Alisaraie; Jordan Patterson; Eric Carpenter; Weiwei Wang; Michael K. Deyholos; et al. (Pharmaceutical Research, 2012)

Forest Management, Engineering, and Operations - Randy Kolka; Matt Powers; John Bradford; Brian Palik; Marty Jurgensen; Dalia Abbas; Tom Gallagher; Stephen Ambagis; Finto Antony; Lewis Jordan; Richard Daniels; Laurie Schimleck; et al. (Journal of Forestry, 2011)
9Forests represent a major global C sink, and forest management strategies that maximize carbon storage offer one avenue for mitigating increases in atmospheric carbon dioxide concentrations. Our understanding of relationships between forest management, productivity, carbon storage, and stand age, however, is limited. We established research plots in a chronosequence of thinned and unmanaged red pine stands in northern Minnesota to study patterns of carbon storage, and the major fluxes that influence carbon sequestration. We completed an inventory of all major C pools across a chronosequence of 57 red pine stands ages 9-306 years on the Chippewa National Forest in the fall of 2009. Results indicate total ecosystem C pools increase as red pine stands age for at least 150 years, and on-site C storage in thinned stands appears similar to unmanaged stands of comparable ages, despite different age-related trends in the live tree and forest floor pools. Thinned stands may have the potential to store more C than unmanaged stands in old age when C removed during harvesting is added into the total ecosystem C pool.

Hydrologic and biotic influences on nitrate removal in a subtropical spring‐fed river - James B. Heffernan; Matthew J. Cohen; Thomas K. Frazer; Ray G. Thomas; Travis J. Rayfield; Jason Gulley; Jonathan B. Martin; Joseph J. Delfino; Wendy D. Graham (Limnology and Oceanography, 2010)
We use a long‐term chemical and hydrologic record in combination with longitudinal sampling and high‐frequency nitrate (NO 3 ‐ ) measurements from in situ sensors to describe temporal and spatial patterns of nitrogen (N) inputs and removal in the spring‐fed Ichetucknee River (Columbia County, Florida) and to determine the hydrological, geomorphic, and biological factors that influence those dynamics. Over a 20‐yr period of record, NO 3 ‐N removal averaged 118 kg N d ‐1 (0.77 g N m ‐2 d ‐1 ) over the upper 5 km of the Ichetucknee River. Three independent estimates of gross autotrophicNassimilation (from gross primary production, diel NO 3 ‐ variation, and standing biomass) agreed closely but accounted for less than 20% of observed N removal. Longitudinal surveys indicate negligible or negative dissolved organic nitrogen and ammonium (NH 4 + ) production, suggesting that denitrification is the predominant mechanism of N removal in this river. A positive relationship between discharge and the magnitude of NO 3 ‐N removal shows that interactions with the surrounding floodplain exert considerable influence at high flows, and longitudinal NO 3 ‐ patterns indicate that N removal may be influenced by channel morphology. These results suggest a greater role for dissimilatory processes and hydrologic connectivity with hyporheic and floodplain sediments than has been previously recognized in highly productive spring‐fed rivers of north Florida. While hydrologic variation is the primary determinant of variation in NO 3 ‐ removal within the Ichetucknee River, comparison across systems indicates that biotic characteristics can cause significant deviation from predictions based on purely physical models of relationships between river size and N removal.

Novel tetranucleotide and pentanucleotide microsatellite loci in the red-cockaded woodpecker (Picoides borealis) - Travis I. Alstad; Brian M. Shamblin; Robert J. Warren; Jonathan M. Stober; L. Mike Conner; Robert J. Cooper; Campbell J. Nairn (Conservation Genetics Resources, 2009)

Trait‐based assembly and phylogenetic structure in northeast Pacific rockfish assemblages - Travis Ingram; Jonathan B. Shurin (Ecology, 2009)
If natural communities are assembled according to deterministic rules, coexisting species will represent a nonrandom subset of the potential species pool. We tested for signatures of assembly rules in the distribution of species' traits in Pacific rockfish ( Sebastes spp.) assemblages. We used morphology, dietary niche (estimated with stable nitrogen isotopes), and distribution data to identify traits that relate to local‐scale resource use (the α‐niche) and to environmental gradients (the β‐niche). We showed that gill raker morphology was related to trophic position (an α‐niche axis), while relative eye size was associated with depth habitat (a β‐niche axis). We therefore hypothesized that, within assemblages of coexisting rockfish species, the gill raker trait would be overdispersed (evenly spaced) due to limiting similarity, while relative eye size would be clustered due to environmental filtering. We examined the evolutionary relatedness of coexisting species to ask whether phylogenetic community structure and trait distributions gave similar indications about the roles of assembly processes. We tested the trait distributions and phylogenetic structure of 30 published rockfish assemblages against a null model of random community assembly. As predicted, the gill raker trait tended to be more evenly spaced than expected by chance, as did overall body size, while relative eye size was more clustered than expected. Phylogenetic community structure appeared to reflect historical dispersal and speciation and did not provide consistent support for assembly rules. Our results indicate that rockfish community assembly is nonrandom with regard to species' traits and show how distinguishing traits related to the α‐ and β‐niches and incorporating functional morphology can provide for powerful tests of assembly rules.